Identifikasi Risiko dan Strategi Mitigasi Risiko pada Proses Pengadaan Direct Material di PT XYZ - Mayasari Tinambunan; Sutrisno Sutrisno (Peneliti.net, 2022)
PT XYZ is a company engaged in the manufacturing industry. PT XYZ has several visions and missions to realize or achieve the goals of the company. In the manufacturing industry, the availability of raw materials or materials is a very important process. The procurement process is the most crucial component of supporting production process activities. To ensure this process runs smoothly, it is necessary to have the ability to anticipate the risks that might occur that could disrupt or hinder the smooth running of the process. Without a good and structured risk management, the impacts of these risks will affect the smooth performance of the company. In identifying the risks that may occur in the procurement process and the proposed mitigation actions that may be carried out, the House of Risk (HOR) method is used. The HOR method is used to solve problems regarding the relationship between risk events, the relationship between risk causes, the relationship between risk and risk causes and risk mitigation actions. In this study, the 5 most crucial causes of risk were found, and then 5 mitigation actions were designed to overcome the impact of these risks.